PENGARUH MACAM BIOCHAR DAN KONSENTRASI ASAP CAIR TERHADAP PENINGKATAN PRODUKSI TANAMAN PADI (Oryza sativa L.) - Mariyatul Qibtiyah; Istiqomah Istiqomah; Harto Harto (Agroteknologi Fakultas Pertanian Universitas Islam Darul 'Ulum (UNISDA), 2022)
In Indonesia, rice (Oryza Sativa L.) has become an important and strategic livelihood. Decreasing soil fertility causes reduced rice production. The use of straw can increase the efficiency of using fertilizers (nitrogen), increase soil fertility through the provision of nutrients in particular (potassium), besides that it can improve the soil. The nutritional content of rice straw is 0.4% Nitrogen, 0.02% Phosphorus, 1.4% Potassium and 5.0% Silicon. This research was conducted in Bulubrangsi Village, Laren District, Lamongan Regency. From February to May 2022. The following research was carried out using the Factorial RAK (Randomized Block Design), which is composed of 2 aspects and each aspect consists of 3 levels. Through these 2 aspects, 9 treatment combinations were obtained and repeated 3 times. The indicators observed in the vegetative phase include: number of leaves and plant height. The indicators observed in the generative phase included: the number of panicles, the fresh weight of the plants, the length of the panicles, the weight of tons per hectare, the weight of 1000 seeds. The data obtained through observation is calculated using analysis of variance using Fisher's test (5% and 1 %) F-test, if there is a significant difference it can be continued using the Least Significant Difference test. The best results in this research were obtained from rice husk biochar and liquid smoke.